Vortex-averaged Arctic ozone depletion in the winter 2002/2003 - Christensen, T.; Knudsen, B. M.; Streibel, M.; Andersen, S. B.; Benesova, A.; Braathen, G.; Claude, H.; Davies, J.; De Backer, H.; Dier, H.; Dorokhov, V.; Gerding, M.; et al. (HAL CCSD, 2004)
International audience A total ozone depletion of 68 Dobson units from 10 December 2002 to 10 March 2003 is derived by the vortex-average method taking into account both diabatic descent of the air masses and transport of air into the vortex. When the vortex is divided into three equal-area regions, the results are 85 DU for the collar region (closest to the edge), 52 DU for the vortex centre and 68 DU for the middle region in between centre and collar.